2017
DOI: 10.7759/cureus.952
|View full text |Cite
|
Sign up to set email alerts
|

Outcome of Percutaneous Release of Tennis Elbow: A Non-Randomized Controlled Trial Study

Abstract: BackgroundTennis elbow is a common disorder of the upper extremity. It can be treated conservatively in the majority of patients, but some resistant cases eventually can be treated by percutaneous release with good functional outcome.Materials and methodsThis non-randomized control trial was conducted at the Department of Orthopaedics Surgery in a tertiary care hospital from July 2015 to June 2016 on 50 patients who underwent percutaneous release of the common extensor origin using an 18 gauge hypodermic needl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…[ 26 ] Surgical management is considered the treatment of choice in this particular cohort of patients. Several surgical techniques like the open release of ECRB,[ 27 ] Nirschl’s procedures,[ 28 ] percutaneous tenotomies,[ 29 ] and even micro-ablation[ 30 ] have been tried. Arthroscopic treatment in such recalcitrant cases has shown to be comparable to open surgical procedures in terms of functional outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…[ 26 ] Surgical management is considered the treatment of choice in this particular cohort of patients. Several surgical techniques like the open release of ECRB,[ 27 ] Nirschl’s procedures,[ 28 ] percutaneous tenotomies,[ 29 ] and even micro-ablation[ 30 ] have been tried. Arthroscopic treatment in such recalcitrant cases has shown to be comparable to open surgical procedures in terms of functional outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Literature review mentions a variety of treatment options for tennis elbow which range from conservative therapy to operative treatment. 1 Surgical intervention can lead to early recovery and return to daily life activities. Extensor tenotomy with various variations has been used by various authors in recent past reporting good to excellent outcomes.…”
Section: Discussionmentioning
confidence: 99%
“…Pathology of condition is unclear, with a variety of conditions being used to explain its aetiology. 1 Most likely, a combination of mechanical overloading and abnormal microvascular changes in the extensor tendon origin esp. extensor carpi radialis brevis are known to contribute to pathology of this condition.…”
Section: Introductionmentioning
confidence: 99%
“…Most studies have not showed any complications. 22 In a study on 18 patients operated using this maneuver, 14 did not show any complications, but this author's histological analysis reported microscopic findings of residual tendinopathy in ten cases had one case who presented paresthesia in the forearm for 14 days after the surgery, with spontaneous improvement. In our study, we found a complication rate of 5% (one case with local alterations of sensitivity in the region of the lateral portal).…”
Section: Postoperative Rehabilitation and Follow Upmentioning
confidence: 92%